A smart robotic adhesive skin using shaped-memory polymers - Li, Yan (Nanyang Technological University, 2023)
In recent years, there has been a significant increase in the popularity of robotic hands leading to a wide range of applications that span across industry, agriculture, and our daily lives. To expand the capabilities of robotic hands, researchers are actively developing smart skin technology. The smart skin, also known as e-skin or intelligent skin, is a thin, flexible, and stretchable structure that can sense and respond to changes in its environment. It endows robotic hands many advanced functionalities such as the sensing capabilities of temperature, pressure, and sliding. One category of smart skin is the adhesive skin, which can provide strong/weak adhesion and has been found to be effective in handling soft, heavy, fragile, or hard objects, thus enhancing both the adaptability and grasping abilities of robotic hands.